2020
DOI: 10.3390/met10050617
|View full text |Cite
|
Sign up to set email alerts
|

New Multistage Sheet-Bulk Metal Forming Process Using Oscillating Tools

Abstract: A new sheet-bulk metal forming process for the production of bulk components out of a flat sheet has been developed. Superimposed oscillation has been applied to the new process. By this means, process limits regarding better mould filling were expanded, and forming forces could be reduced. In order to investigate the effects of superimposed oscillation on material behaviour, plane strain and ring compression tests were carried out. The superimposed oscillated plane strain compression test showed a reduction i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…In this research, the effects of a superimposed oscillated pre-stretching on the fatigue strength, strain hardening, and structural properties of tensile test specimens made of the materials DC04 and DP600 were investigated. Since a superimposed oscillation has a high potential according to an extension of forming limits [13], a better understanding of the effects of a superimposed oscillation on the fatigue strength and strain hardening is of high importance. It was found that the fatigue strength behavior, strain hardening, and the influence on the microstructure of the materials DC04 and DP600 can be influenced differently by a superimposed oscillation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this research, the effects of a superimposed oscillated pre-stretching on the fatigue strength, strain hardening, and structural properties of tensile test specimens made of the materials DC04 and DP600 were investigated. Since a superimposed oscillation has a high potential according to an extension of forming limits [13], a better understanding of the effects of a superimposed oscillation on the fatigue strength and strain hardening is of high importance. It was found that the fatigue strength behavior, strain hardening, and the influence on the microstructure of the materials DC04 and DP600 can be influenced differently by a superimposed oscillation.…”
Section: Discussionmentioning
confidence: 99%
“…Since the high potential of superimposed oscillated-forming processes on effects such as increasing the surface quality [12] and improving the form-filling [13] of components has been demonstrated in previous studies, this technology has promising application possibilities. Especially in the new technology of sheet-bulk metal forming, which aims at the production of complex functional components with secondary forming elements made of thin sheets [14], superimposed oscillated forming offers the interesting possibility of extending the production limits of this technology.…”
Section: Introductionmentioning
confidence: 99%
“… Multi-stage sheet-bulk metal forming (SBMF) process for the production of components with rotationally symmetrical external gearing [ 5 ]. ( a ) Initial state; ( b ) Deep drawing; ( c ) Compression and shear cut.…”
Section: Figurementioning
confidence: 99%
“…SBMF processes combine numerous methods of forming technology. As an example of such a process, a stage sequence for the production of a component with internal and external gearing is shown in Figure 1 [ 5 ]. In this process, a cup is first deep-drawn from a 4 mm wide round blank.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation